2020
DOI: 10.1002/ijop.12653
|View full text |Cite
|
Sign up to set email alerts
|

Growing Together—Effects of a school‐based intervention promoting positive self‐beliefs and social integration in recently immigrated children

Abstract: We present a school‐based intervention geared to foster the social integration of recently immigrated (RI) primary school children by creating repeated positive contact situations with classmates brought up in the receiving society. Coaches encouraged groups of tandems, consisting of one RI and one child brought up in Germany each, to engage in cooperative activities designed to strengthen positive self‐beliefs and perception of equal status. In a quasi‐experimental control‐group design (N = 318), we compared … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…More recently, Hannover et al. (2020) implemented a school‐based intervention program to support the social integration of newcomer immigrant children aged 9–10 years old in primary schools in Germany. Based on the creation of tandems with native peers, the aim of this intervention was to create “repeated positive contact situations” (p. 713).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Hannover et al. (2020) implemented a school‐based intervention program to support the social integration of newcomer immigrant children aged 9–10 years old in primary schools in Germany. Based on the creation of tandems with native peers, the aim of this intervention was to create “repeated positive contact situations” (p. 713).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies proved the expectation that feelings of relatedness to peers in school are closely linked to students' academic achievement as well as to outcomes like academic motivation, intrinsic and utility values, or achievement goal orientations (e. g., Gillen-O'Neel & Fuligni, 2013;Looser, 2009;Vanwynsberghe et al, 2017). Intervention studies promoting students' sense of social belonging in school were found to increase, for example, academic achievement and positive self-beliefs of minority group students (e. g., Hannover et al, 2020;Walton & Cohen, 2011). Contrarily, feelings of aloneness or social exclusion were found to be related to a decrease in cognitive performance and graduation test scores (Baumeister et al, 2002).…”
Section: Peer Relations and Their Correlatesmentioning
confidence: 99%